Investigation of Global Annual Temperature Anomalies and Statistical Inferences Based On It - Važnevičiūtė, Julija; Kligienė, Nerutė (Lithuanian Journal of Statistics, 2011)
Global warming problem earlier investigated mostly by scientists in climatology, now attract the attention of manyresearchers because a changing climate cause a great anxiety. The paper analyses the data of North and South hemisphere temperaturesvariation and North and South hemisphere temperatures 5 years average variation. The data collected by the National Aeronauticsand Space Administration since 1880 year are analyzed as time series in this paper. The ARMA models are fitted, their statisticalcharacteristics evaluated and predictions for future values have been calculated using the fitted models of one dimensional and multidimensionalautoregressive models. Calculated predicted values were compared to really observed values and the research resulted inthe best fitted autoregressive and moving average models well describing the global warming data.